SEG Technical Program Expanded Abstracts 2009 2009
DOI: 10.1190/1.3255818
|View full text |Cite
|
Sign up to set email alerts
|

Improving seismic calibration and geomechanical models through characterization of anisotropy using single and multi well data: Case Study in Forties Field, UK

Abstract: Extending the life of mature fields is dependant on reducing cost of operations (drilling & completions) and choosing locations for optimized production. Understanding the implications of anisotropy helps in reducing the uncertainty of wellbore stability models and improving seismic calibration. A major difficulty in extending seismic and sonic processing for geomechanical and geophysical applications within anisotropic media is the determination of an anisotropic velocity model. However, mature fields, where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…A full sensitivity analysis of the Draupne shales was performed to assess the stability of the shales at varying drilling angles while the rock strength of the shales was also examined as studies have shown the strength of anisotropic shales can greatly reduce by up to 85% when being drilled close to 45 degrees. 12 The sensitivity analysis looked to assess the potential of the Draupne shales reducing the strength due the angle of the hole and the subsequent influence on the well bore stability through this section. The planned mud weight of 1.39sg was used to drill out the shoe and the section.…”
Section: ½" Hole Sectionmentioning
confidence: 99%
“…A full sensitivity analysis of the Draupne shales was performed to assess the stability of the shales at varying drilling angles while the rock strength of the shales was also examined as studies have shown the strength of anisotropic shales can greatly reduce by up to 85% when being drilled close to 45 degrees. 12 The sensitivity analysis looked to assess the potential of the Draupne shales reducing the strength due the angle of the hole and the subsequent influence on the well bore stability through this section. The planned mud weight of 1.39sg was used to drill out the shoe and the section.…”
Section: ½" Hole Sectionmentioning
confidence: 99%